Mycobacterium tuberculosis Rv2626c‐derived peptide as a therapeutic agent for sepsis. Issue 12 (1st December 2020) - Kim, Sun Young; Kim, Donggyu; Kim, Sojin; Lee, Daeun; Mun, Seok‐Jun; Cho, Euni; Son, Wooic; Jang, Kiseok; Yang, Chul‐Su
Abstract: The Rv2626c protein of Mycobacterium tuberculosis is a promising vaccine candidate owing to its strong serum antibody response in patients with tuberculosis. However, there is limited information regarding the intracellular response induced by Rv2626c in macrophages. In this study, we demonstrated that Rv2626c interacts with the RING domain of TRAF6 and inhibits lysine (K) 63‐linked polyubiquitination of TRAF6 (E3 ubiquitin ligase activity); this results in the suppression of TLR4 inflammatory signaling in macrophages. Furthermore, we showed that the C‐terminal 123–131‐amino acid Rv2626c motif promotes macrophage recruitment, phagocytosis, M2 macrophage polarization, and subsequent bacterial clearance. We developed rRv2626c‐CA, a conjugated peptide containing the C‐terminal 123–131‐amino acid Rv2626c that targets macrophages, penetrates the cell membrane, and has demonstrated significant therapeutic effects in a mouse model of cecal ligation and puncture‐induced sepsis. This multifunctional rRv2626c‐CA has considerably improved potency, with an IC50 that is 250‐fold ( in vitro ) or 1, 000‐fold ( in vivo ) lower than that of rRv2626c‐WT. We provide evidence for new peptide‐based drugs with anti‐inflammatory and antibacterial properties for the treatment of sepsis. SYNOPSIS: rRv2626c‐CA, a macrophages‐targeted tetrapeptide‐conjugated protein composed of 9 amino acids of Rv2626c, is shown here to be the first therapeutic protein to regulate immune response and bacteria growth in the TLR4 signaling pathway for treatment of sepsis. The Rv2626c peptide specifically binds to TRAF6 and inhibits the E3 ubiquitin ligase TRAF6‐mediated TLR4 signaling. Intraperitoneal administration of rRv2626c‐CA protects mice from CLP‐induced sepsis by inhibiting pro‐inflammatory cytokine production and promoting bacteria clearance. C‐terminal 123–131‐amino acid motif of Rv2626c promotes anti‐inflammation, macrophage recruitment, phagocytosis, M2 macrophage polarization, and subsequent bacterial clearance. Abstract : rRv2626c‐CA, a macrophages‐targeted tetrapeptide‐conjugated protein composed of 9 amino acids of Rv2626c, is shown here to be the first therapeutic protein to regulate immune response and bacteria growth in the TLR4 signaling pathway for treatment of sepsis.